Cover Picture: Carboranes as Aryl Mimetics in Catalysis: A Highly Active Zwitterionic NHC‐Precatalyst (Chem. Eur. J. 33/2017). Issue 33 (7th April 2017) - Selg, Christoph; Neumann, Wilma; Lönnecke, Peter; Hey‐Hawkins, Evamarie; Zeitler, Kirsten
Abstract : A new offspring of the organocatalyst family has hatched from the merger of covalent catalysis and a carborane as an aryl‐mimetic replacement: the novel zwitterionic triazolium based N‐heterocyclic carbene (NHC) precatalyst bears a 7, 8‐dicarba‐ nido ‐undecaboranyl substituent (nidus ( lat .)=nest) and offers excellent activity and broad applicability in a wide range of organocatalytic transformations. The straightforward synthesis and a detailed comparison to recent aryl‐based precatalysts provides useful insights to pave the way for further development of this unprecedented class of catalysts. More information can be found in the Full Paper by K. Zeitler et al. onpage 7932 .